The Effect Of Solvency And Prior Opinion On The Acceptance Of Modified Audit Opinion On Going Concern With Company Size As A Moderating Variable - Christine Rodesya (Jurnal Al-Iqtishad, 2026)
This study aims to test and analyze whether the effect of Solvency and Prior Opinion on the Acceptance of Modified Audit Opinions on Going Concern with Company Size as a Moderating Variable. The population in this study were all infrastructure companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The sample selection in this study used purposive sampling method. This hypothesis testing using logistic regression analysis was carried out with the help of the SPSS 27 program. The samples selected in this study were 23 companies and were selected based on predetermined criteria. Data obtained through data from the official website of the Indonesia Stock Exchange and other related websites and studying literature related to research problems. The results showed that solvency affects the modified audit opinion on going concern with a significant value of 0,043 < 0,05. Prior opinion affects the modified audit opinion on going concern with a significant value of 0,001 < 0,05. Company size is able to moderate the effect of solvency on modified audit opinion on going concern with a significance value of 0,001 < 0,05. But company size is not able to moderate the prior opinion on the modified audit opinion on going concern with a significance value of 0,188 > 0,05.